The Aftermath of Suffrage - Gottlieb, Julie V. author. aut Link
X, 254 p.
Keywords: This collection explores the aftermath of the Representation of the People Act, which gave some British women the vote. Experts examine the paths taken by both former-suffragists as well as their anti-suffragist adversaries, the practices of suffrage commemoration, and the changing priorities and formations of British feminism in this era.